The New Cambridge History of India 1 :7: Architecture and Art of the Deccan Sultanates - Singh, David Emmanuel (Journal of Dharma, 1999)
George Michell and Mark Zebrowsky, The New Cambridge History of India 1 :7: Architecture and Art of the Deccan Sultanates, Cabridge: University Press, 1999